(untitled) (Eurasian Research Bulletin, 2022)
The article discusses ways to improve the effectiveness of the educational process in preparing students for work and professional activities. The author notes the importance of forming a conscious attitude to work and study, and provides relevant examples on information technology training that meet modern requirements and standards